Additive effect on pulmonary function and disability of intensive pulmonary rehabilitation following bronchoscopy lung volume reduction (BLVR) for severe emphysema. (October 2018) - Bianchi, Luca; Bezzi, Michela; Berlendis, Marialma; Marino, Simona; Montini, Alessandra; Paneroni, Mara; Novali, Mauro; Steinhilber, Gundi; Vitacca, Michele
Abstract: Background: Pulmonary rehabilitation (PR) is mandatory before bronchoscopy lung volume reduction (BLVR); there is scant information about its efficacy post-BLVR. We retrospectively evaluated pulmonary function (PF) and disability in patients pre/post-BLVR and its additive effect on an intensive PR program post-BLVR vs matched non-BLVR controls. We analyzed changes within BLVR patients according to presence or not of atelectasis. Methods: We compared PF and exercise tolerance (6-min walk test, 6MWT) in 39 BLVR patients (FEV1 % pred. 28.9 ± 1.5; RV% pred. 236.1 ± 7.7) pre-/post-BLVR, and vs. 32 controls (FEV1 % pred. 32.7 ± 1.5; RV % pred. 217.8 ± 8.3) before and after PR. Results: BLVR patients showed a greater improvement than controls in PF (difference between groups: 3.8 for FEV1 % pred., p = 0.043; −20.5 for RV % pred., p = 0.02) and 6MWT response rate (12/39 vs. 1/39 subjects, p = 0.003). Both groups further improved significantly 6MWT after PR without a significant difference between groups. Atelectasis after BLVR mainly accounted for the improvement in FEV1 % pred, RV% pred. and 6MWT compared to both BLVR without atelectasis and controls. Conclusion: BLVR improves PF (particularly RV) and exercise tolerance, patients with lobar exclusion being the best improvers. PR following BLVR yields a further improvement in exercise tolerance in both (atelectasis and non-atelectasis) subgroups.